2012
DOI: 10.1371/journal.pone.0048791
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Induces Cutaneous Wound Healing In Vivo and Enhances Keratinocyte Motility

Abstract: BackgroundCutaneous wound healing is a complex process involving several signaling pathways such as the Wnt and extracellular signal-regulated kinase (ERK) signaling pathways. Valproic acid (VPA) is a commonly used antiepileptic drug that acts on these signaling pathways; however, the effect of VPA on cutaneous wound healing is unknown.Methods and FindingsWe created full-thickness wounds on the backs of C3H mice and then applied VPA. After 7 d, we observed marked healing and reduced wound size in VPA-treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 53 publications
4
48
1
1
Order By: Relevance
“…The Erk and Akt signaling pathways, which are known to be crucial in cutaneous wound healing [22,33], can be modulated by numerous agents [18,19,21], including 17 β-estradiol [23]. Moreover, their roles in promoting cell proliferation have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Erk and Akt signaling pathways, which are known to be crucial in cutaneous wound healing [22,33], can be modulated by numerous agents [18,19,21], including 17 β-estradiol [23]. Moreover, their roles in promoting cell proliferation have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect was more pronounced with topical treatment as compared to oral administration. Increased cellular proliferation is an essential aspect of wound healing (Lee et al, 2012). Increased cellular proliferation in the study demonstrated early wound healing in treated animals as compared to control while decline in Ki67 expression may due to the fact that cellular proliferation might have been subsided as a result of transit from proliferation phase to remodeling phase (Xian et al, 2015) which was evident from the study as topical treatment exhibited highly significant decrease in cellular proliferation on 14th day produced earlier wound healing on 20th day as compared to oral treatment where complete wound healing was achieved on 22nd day.…”
Section: Discussionmentioning
confidence: 99%
“…59 The active keratinocyte proliferation and fast re-epithelialization are important for the new tissue regeneration, while the bacterial infection is the main cause of impaired healing. 1,59,60 Wound dressings impregnated with antimicrobials can prevent local bacterial infection and maintain the natural microenvironment for cell proliferation and tissue regeneration to promote wound healing. 3,61 As described earlier, compared with the control, PCL and PCL/DA groups, the biocompatible PCL/NS1.0 was efficient to protect the wounds from bacterial infection ( Figure 9) and maintain a natural and aseptic wound microenvironment without severe inflammation response to promote keratinocyte proliferation (Figures 11 and 12).…”
mentioning
confidence: 99%